Association between Copeptin and Metabolic Syndrome: A Systematic Review - Ricardo Rojas-Humpire; David R. Soriano-Moreno; Brenda Galindo-Yllu; Jessica Hanae Zafra-Tanaka (Journal of Nutrition and Metabolism)
Background. Copeptin, a reliable marker for vasopressin release, has been associated with cardiometabolic diseases including metabolic syndrome (MetS). This systematic review aims to evaluate the association between copeptin and MetS. Methods. We searched in Pubmed, Scopus, EMBASE, and Web of Science databases until March 2021 and included observational studies (cohort studies, cross-sectional, and case-control) reporting the risk or prevalence of having MetS in patients with elevated copeptin levels compared to patients without elevated copeptin levels. The risk of bias was evaluated with the Newcastle-Ottawa Scale. Meta-analysis was not performed because of the heterogeneity of the copeptin cut-off values. Results. A total of 7 studies (5 cross-sectional, 1 case-control, and 1 cohort) were included comprising 11,699 participants. Most of them were performed in the adult general population. Two cross-sectional and one case-control studies found a positive significant association between higher levels of copeptin and MetS. While three cross-sectional and one cohort studies found no association. The case-control study had several methodological limitations, most cross-sectional studies were methodologically adequate and the cohort study had no methodological issues. Conclusions. The association between copeptin and MetS is inconsistent. However, the arginine-vasopressin system impairment contributes to metabolic disorders, expressing plasma copeptin changes. Thus, more longitudinal studies are required to corroborate the association of copeptin and MetS.